2016
DOI: 10.4102/sajim.v18i1.721
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into users' information security awareness on social networks in south western Nigeria

Abstract: Background: Social networks (SNs) offer new and exciting opportunities for interaction among people, cutting across different stratum of the society and providing a ubiquitous mechanism that supports a wide variety of activities. They are at the same time being exploited by criminals to fraudulently obtain information from unsuspecting users. Unfortunately, the seamless communication and semblance of safety assumed by most users make them oblivious to the potential online dangers.Objective: Using quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The first literature category focuses on CSA among individuals in society and employees in organizations. Okesola et al (2016) used quantitative methods to assess an individual's level of awareness of cybersecurity risks in southwest Nigeria and found that most users of social networks, especially female users, have low CSA. Grassegger and Nedbal (2021) stated that focusing only on technical measures is not enough to ensure the information security for the organizations, and improving ISA for all employees is also essential.…”
Section: Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first literature category focuses on CSA among individuals in society and employees in organizations. Okesola et al (2016) used quantitative methods to assess an individual's level of awareness of cybersecurity risks in southwest Nigeria and found that most users of social networks, especially female users, have low CSA. Grassegger and Nedbal (2021) stated that focusing only on technical measures is not enough to ensure the information security for the organizations, and improving ISA for all employees is also essential.…”
Section: Related Studiesmentioning
confidence: 99%
“…This study investigates the cybersecurity awareness of usage habits from the perspectives of http and device usage, as they are typical Internet user activities. According to Okesola et al (2016), even though the good function of social media for many activities has continued to develop in recent years, malicious users and hackers have also continued to utilize them as a covert means of assaulting and abusing unwary and ignorant individuals. In terms of cybersecurity education, the purpose of this study is to evaluate college students' perspectives and evaluations of the cyber security education provided by their colleges and institutions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%